The Assessment of Diagnostic Accuracy of Real Time Shear Wave Elastography in Detecting Liver Cirrhosis Keeping Histopathology as Reference Standard - Saleem, Sultan; Slehria, Attique ur Rehman; Rauf, Muhammad Haris; Sohail, Marium; Taufiq, Nida; Khan, Muhammad Usman (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the diagnostic accuracy of real-time Shear Wave Elastography (SWE) in detecting liver cirrhosis among patients suffering from diseases predisposing to it, keeping histopathology as the reference standard. Study Design: Cross-sectional study. Place and Duration of Study: Armed Forces Institute of Radiology and Imaging, Rawalpindi, from Jan 2018 to Jul 2018. Methodology: A total of 114 patients were recruited, and relevant history taken from patientsreal-time shear wave elastography (SWE) of the liver was performed, followed by USG guided liver biopsy. Patients having clinically suspected diseases predisposing to hepatic fibrosis were sent to the Radiology department for ultrasound or ultrasound-guided liver biopsy. Elasticity values using sheer waves of 14.9 kPa (2.23m/s) or more was taken as suggestive of cirrhosis. Elastography findings were compared with histopathology findings. Results: Real-time SWE showed high diagnostic accuracy for detecting liver cirrhosis with sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of 92.86%, 89.66%, 89.66%, 92.86% and 91.23%, respectively. Conclusion: This study concluded that the diagnostic accuracy of RTSW elastography in detecting liver cirrhosis is relatively high.